The role of erenumab in the treatment of migraine - Anna P. Andreou; Matteo Fuccaro; Giorgio Lambru (Therapeutic Advances in Neurological Disorders, 2020)
Calcitonin gene related peptide (CGRP) monoclonal antibodies (mAbs) have been the first class of specifically developed preventive treatments for migraine. Clinical trials data suggest superiority of the CGRP mAbs to placebo in terms of prevention of migraine symptoms, migraine-specific quality of life and headache related disability. Treatment-related side effects overall did not differ significantly from placebo and discontinuation rate due to side effects has been low across the clinical trials, perhaps in view of their peripheral mode of action. Along with their route and frequency of administration, these novel class of drugs may constitute an improvement compared with the established arsenal of migraine treatments. Erenumab is a fully human antibody and the only mAb acting on the CGRP pathway by blocking its receptor. It is the first of the CGRP mAb class approved by the US Food and Drug Administration (May 2018) and the European Medicines Agency (July 2018). Erenumab exists in two different doses (70 mg and 140 mg) and it is administered with monthly subcutaneous injections. This review summarises erenumab pharmacological characteristics, clinical trials data, focusing on the potential role of this treatment in clinical practice.